Strategi Efektif dalam Pelatihan Persiapan Konten Digital untuk Pemula : Meningkatkan Keterampilan Marketing di Era Digital - Amanda Mutiara Hasibuan; Zuhrinal M. Nawawi (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
This study aims to identify and analyze effective strategies in digital content preparation training for beginners to enhance marketing skills in the digital era. The method used is a qualitative literature review examining various literatures, reports, and empirical studies related to digital marketing skill development. The findings indicate that project-based and case study training methods are the most effective in improving beginners’ technical and creative abilities, especially in content creation and social media management. Major challenges faced by beginners include information overload, lack of practical experience, and rapid algorithm changes. Quality and interactive content proves to be the key to successful digital marketing, while performance measurement using appropriate metrics and analytic tools is crucial for strategy evaluation and development. Social media remains the primary platform with great potential, supported by optimization strategies involving active interaction and influencer collaboration. Continuous learning and integration of digital and traditional marketing through an omnichannel approach strengthen overall marketing effectiveness. This study contributes significantly to the development of adaptive and holistic training programs and digital marketing strategies for beginners.